2013
DOI: 10.1007/s10152-013-0346-3
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding reveals a cryptic nemertean invasion in Atlantic and Mediterranean waters

Abstract: For several groups, like nemerteans, morphologybased identification is a hard discipline, but DNA barcoding may help non-experts in the identification process. In this study, DNA barcoding is used to reveal the cryptic invasion of Pacific Cephalothrix cf. simula into Atlantic and Mediterranean coasts. Although DNA barcoding is a promising method for the identification of Nemertea, only 6 % of the known number of nemertean species is currently associated with a correct DNA barcode. Therefore, additional morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 26 publications
1
40
0
Order By: Relevance
“…For these reasons a continuous monitoring action is necessary to provide information about the costal structure, sea level changes, spatio-temporal species in the caves performed by a census made and supported by professional divers and molecular techniques [8][9][10][11][12]. In this optic the census and the identification represent an important step to establish the abundance/rarity degree of the marinea species [13,14], as well to detect possibly cryptic species and even to describe new species [15][16][17]. The newest EU political actions regarding maritime strategic objectives, such as the Marine Strategy Framework Directive (MSFD), and the European Strategy for Marine and Maritime Research [18], represent a push to draw up an inventory of the alien species in the Mediterranean sea.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons a continuous monitoring action is necessary to provide information about the costal structure, sea level changes, spatio-temporal species in the caves performed by a census made and supported by professional divers and molecular techniques [8][9][10][11][12]. In this optic the census and the identification represent an important step to establish the abundance/rarity degree of the marinea species [13,14], as well to detect possibly cryptic species and even to describe new species [15][16][17]. The newest EU political actions regarding maritime strategic objectives, such as the Marine Strategy Framework Directive (MSFD), and the European Strategy for Marine and Maritime Research [18], represent a push to draw up an inventory of the alien species in the Mediterranean sea.…”
Section: Introductionmentioning
confidence: 99%
“…This DNA barcode is the sequence of the ''Folmer fragment'' [28], a polymorphic part of the mitochondrial Cytochrome Oxidase subunit I gene (COI), which can be used to identify closely related species as well as higher taxa in many animal phyla. Additional studies have shown that genetic identification by ''COI barcodes'' can provide a useful tool to detect possibly cryptic species, to describe new species and to discuss evolutionary implications [15]. The "Grotta del Maresciallo" cave, even if it's less famous than the neighboring ones (such as the "Grotta del Turco"), presents a high variety of species, that's why the objectives of this study have been to describe relative spatial patterns of quantitative distribution and relative abundance of species; to calculate the percentage contribution of a single group to the total Mediterranean marine cave diversity, to verify the possibility to identify species by using barcoding as complementary taxonomy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, molecular methods have been a useful tool for ascertaining the actual biodiversity of these worms and increasing our knowledge of several of the problematic species (Chen et al 2010;Fernández-Álvarez and Machordom 2013;Kvist et al 2013). The nemertean genus Malacobdella de Blainville 1827 originally contained 13 nominal species, of which six are currently regarded as valid (Gibson 1995;Ivanov et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, the most complete morphological description of M. grossa, reported by Riepen (1933), was based on material from Arctica islandica (Linnaeus 1767) (Heterodonta: Arcticoidea). Nemerteans are traditionally identified and classified using morphological criteria, but the relatively low number of qualitative morphological characters, the lack of adequate fixation procedures for histological studies, vague descriptions in the original papers and the paucity of species-specific characters make species delimitation problematic, especially when comparing closely related species (Chen et al 2010;Fernández-Álvarez and Machordom 2013;Kvist et al 2013). The difficulty of morphological recognition of a great part of the more than 1,280 species included in the phylum Nemertea has been previously discussed (Andrade et al 2012;Kvist et al 2013, among others), and different authors have advocated new tools and comprehensive studies for correctly identifying species and thus providing accurate biodiversity knowledge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation